Development of a prototype of web based car rental system using data matching technique / Fariza Hamzan - Hamzan, Fariza (2006)
Nowadays, there are online car reservations which give much benefit to user. The existing of this online system, can. overcome the problem of availability and provide convenience to. the user in renting, car. Yet users still need more convenience system such as helping them in recommending car to be rent based on their specific requirements. Data matching technique is applied to the system to fulfill their needs. The system will match the data entered by users to advice or recommend car to be rented. The data includes the user budget, number of passenger and distance. However, user may choose either to accept the recommendation or they can view the car catalogue provided by the system to choose by their own. They can select their preferred car from the car catalogue. Reservation can be done through online and users have to come to the service center to make payment and pick the reserved car. This system is functioned in retrieving, creating, updating and deleting the data or information depends on the security level and allows the organization to search user information from the database based on their identification card number. Besides that, this system may produce reports such as payment receipt, renting information and statistics of car renting by year, month, or week. The finding of this project is the web-based car rental system with recommended car to be rent and the output that will produce the information by following the user requirements. In conclusion, the system may need some enhancement and improvement in the fixture.